Developing a veterinary professional “identity”: first year veterinary students’ perspectives on how they describe themselves now and as future veterinarians: 2017–2024 - Bagley, Rodney S.; Carnevale, Joyce; Mindthoff, Amelia (Frontiers in Veterinary Science, 2025)
IntroductionAs an assignment in an introductory course to the profession, we asked first year veterinary students in their initial (fall) semester to identify words that they would use to describe themselves now and how they want to be described in the future as veterinarians.MethodsUsing a Qualtrics survey instrument, students were asked to record five descriptive words in response to each of the following prompts: “How would you describe yourself?”, “How would you like your future veterinary colleagues to describe you?”, and “How would you like your future clients to describe you?” Students’ responses were collected beginning in fall of 2017 (Class of 2021) through fall of 2024 (Class of 2028). Word choices were collated and ranked based on the number of times an individual word was recorded.ResultsWhile there was some variability from year to year, the five most common word choices for the prompt “How would you describe yourself?” were: “Hard-working”, “Kind”, “Caring”, “Compassionate”, and “Determined”. The five most common word choices for the prompt “How would you like your future veterinary colleagues to describe you?” were: “Hard-working”, “Compassionate”, “Knowledgeable”, “Caring”, and “Reliable”. The five most common word choices for the prompt “How would you like your future clients to describe you?” were: “Compassionate,” “Knowledgeable”, “Caring”, “Kind”, and “Empathetic”. The recorded rank for the most common descriptive word changed slightly over the study time to the prompts “how would you describe yourself” and the “how would you want your colleagues to describe you”, but not the “how would you want your clients to describe you” prompt.DiscussionThese collective student responses provide insight into the origin of their veterinary “identity” as they enter the veterinary curriculum to become veterinarian professionals.